2010
DOI: 10.4104/pcrj.2010.00005
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function testing in the Emergency Department and medications prescribed at discharge: results of the Multinational Acute asthma Management, Burden, and Outcomes (MAMBO) study

Abstract: Aims: To evaluate asthma care in the emergency department (ED), including use of pulmonary function testing (PFT) and how patients are treated when discharged.Methods: Internet-based surveys were completed by 298 healthcare practitioners in seven countries on 1078 patients 15-70 years old with an acute asthma exacerbation.Results: Less than 60% of patients received guideline-recommended therapy with a bronchodilator, corticosteroid, and supplemental oxygen. Patients undergoing PFT had significantly more course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A multi-national study on acute asthma management, burden, and outcomes also revealed that <60% of the patients received guideline-recommended therapy with a BD, CS, and supplemental oxygen 23. Oxygen administration is low in this study because there is a lack of assessment of the oximetry status and indication for acute oxygen administration during the initial assessment on admission.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A multi-national study on acute asthma management, burden, and outcomes also revealed that <60% of the patients received guideline-recommended therapy with a BD, CS, and supplemental oxygen 23. Oxygen administration is low in this study because there is a lack of assessment of the oximetry status and indication for acute oxygen administration during the initial assessment on admission.…”
Section: Discussionmentioning
confidence: 82%
“…Functional assessment components such as oxygen saturation and PEFR were measured in 5.9% and 5.0% of the cases, respectively; these indices are comparatively <93.0% and 20% in Spain24 and 96.1% and 81.0% in the UK,18 respectively. PEFR is less commonly assessed in Mexico and Italy and more commonly assessed in Australia and France 23. None of the cases had their post-BD PEFR and this is in contrast to 38.0% reported in the UK which is also a disappointing result 18.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, in 2010 Fitzgerald and colleagues, using an Internet-based survey, evaluated the use of pulmonary function testing in the emergency departments of hospitals in 7 countries. 25 Based on the responses of 298 healthcare providers and 1,078 patients, ages 15 to 70, the authors found that among patients who underwent pulmonary function testing, only 11% had FEV 1 , 12% had both PEF and FEV 1 , and the rest had only PEF measured. Forty-four percent of patients with moderate or severe exacerbations did not have any spirometric testing performed.…”
Section: What Is the Role Of Spirometry And D Lco In Hospitalized Patmentioning
confidence: 99%
“…However, these parameters have not been assessed systematically and are therefore just general guides [1,9]. It needs to be emphasized that adherence to guidelines on asthma management is poor [34 ]. Therefore, a suitable definition for clinical practice has to be prospective.…”
Section: Key Pointsmentioning
confidence: 99%